Bullying and cyberbullying what every educator needs to know - Englander, Elizabeth Kandel (Harvard Education Press, 2013)
"Bullying is a term that's being, well, bullied. It's been rendered essentially powerless by being constantly kicked around," writes nationally recognized bullying expert Elizabeth Kandel Englander. In this practical and insightful book, Englander dispels pervasive myths and misconceptions about peer cruelty, bullying, and cyberbullying. Drawing on her own and others' research, she shows how educators can flag problematic behaviors and frame effective responses. Englander puts a special focus on "gateway" behaviors--those subtle actions that, unchecked, can quickly escalate into more serious misbehavior--and explores how students perceive their own and their peers' behavior. Written in an accessible, conversational tone and informed by careful research, this timely book is an essential guide for educators. Key takeaways include the impact of technology on social behavior, a framework for responding effectively to bullies--including innovative ideas about the role of social peers--and suggestions for working with parents. -- Publisher description.